2021
DOI: 10.1177/23328584211039467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Immigration Enforcement on School Engagement: Evidence From 287(g) Programs in North Carolina

Abstract: During the past 15 years, immigration enforcement increased dramatically in the U.S. interior. There is a growing recognition that immigration enforcement in the U.S. interior has spillover effects onto U.S. citizens. I examine the impacts of a type of partnership between Immigration and Customs Enforcement and local law enforcement, 287(g) programs, on school engagement within North Carolina. In North Carolina, nine counties were approved to establish 287(g) programs, and another 15 applied but were not appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Consistent with prior research (Bellows, 2021; Kirksey, 2020; Kirksey & Sattin‐Bajaj, 2021; Kirksey et al., 2020), we observed a substantial spike of nearly 15 percentage points in COI student daily absence rates in the week immediately following the raid in Hamblen County, and an estimated 33 percent increase in the monthly absence rate in the raid month compared to average absence rates in prior Aprils. Our estimate of the immediate increase in student absences is closer in magnitude to that of Kirksey (2020), who specifically investigated incidents involving high numbers of immigration arrests.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with prior research (Bellows, 2021; Kirksey, 2020; Kirksey & Sattin‐Bajaj, 2021; Kirksey et al., 2020), we observed a substantial spike of nearly 15 percentage points in COI student daily absence rates in the week immediately following the raid in Hamblen County, and an estimated 33 percent increase in the monthly absence rate in the raid month compared to average absence rates in prior Aprils. Our estimate of the immediate increase in student absences is closer in magnitude to that of Kirksey (2020), who specifically investigated incidents involving high numbers of immigration arrests.…”
Section: Discussionsupporting
confidence: 90%
“…These additional burdens borne by children living with unauthorized family members also affect their educational engagement, with research showing that they are more likely to be disruptive in the classroom, absent from school, held back to repeat a grade, or to drop out of school (Amuedo-Dorantes & Lopez, 2015;Bellows, 2021;Capps et al 2007;Chaudry et al 2010;Kirksey & Sattin-Bajaj, 2021). Amuedo-Dorantes and Lopez (2015) examined the intensification of interior immigration enforcement in the U.S. and found that its largest negative impacts were on younger children, ages 6 to 13 years, whose probability of repeating a grade rose by 6 percent and likelihood of dropping out of school increased by a staggering 25.2 percent.…”
Section: Evidence Base On the Consequences Of Immigration Enforcement...mentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of research shows that adoption of these two programs reduced public school enrollment of Hispanic children (Amuedo-Dorantes and Lopez 2015; Dee and Murphy 2020), decreased the average achievement of Hispanic and Black students (Amuedo-Dorantes and Lopez 2015; Bellows 2021), raised poverty levels (e.g., Amuedo-Dorantes et al 2018), and increased the food and housing insecurity of Hispanic households (e.g., Amuedo-Dorantes et al 2018;Potochnick et al 2017;Rugh and Hall 2016). Additional research demonstrates that apprehensions and detentions by Customs and Border Protection agents along the border (e.g., Amuedo-Dorantes et al 2021;Brabeck and Xu 2010;Patler and Gonzalez 2021) and immigration raids conducted by U.S. Immigration and Customs Enforcement (e.g., Amuedo-Dorantes and Antman 2022; Bellows 2021;Capps et al 2007;Lopez et al 2017;Novak et al 2017;Santillano et al 2020) negatively affect the social and economic outcomes of immigrant families.…”
Section: Policing Crimmigration and The Education Of Undocumented Stu...mentioning
confidence: 98%